THE RESOLUTION OF DOMESTIC VIOLENCE IN THAILAND - Ariyapachpol, Rathavich; Woraphattirakul, Paphatsorn (Journal of Buddhist Anthropology, 2020)
This research article aimed to study situation of domestic violence in Thailand and provided for solution on how to make the strategy plans on the resolution of domestic violence in Thailand. This qualitative research article has analyzed content by collecting data from a focus group discussion and in-depth interview of 22 key informants residing in Bangkok of which the in-depth interviews were comprised of 7 public officials, 1 private enterprise, and 6 academics and the focus group was comprised of 8 victims of domestic violence. It was found from this research that the problems and the resolution of domestic violence in Thailand were: Physical violence of which the problems were based on the tradition of men power control could be lessened by providing the knowledge of the domestic violence situation; Sexual violence included both sexual harassment and sexual assault could be lessened by educating the children in sexual prevention and increased more legal protection; Mental or Social violation which was mostly based on irony speech could be lessened by instilling values in childhood; Economic violence which was mostly come from the weak economic families could be lessened by providing the careers or income, supporting the community fund and fostering the community products. The appropriate authorities shall emphasize the strategy plans to tackle with the problems of domestic violence in Thailand in 5 approaches: creating women community development organizations; fostering the self-development programs; promoting family development learning; supporting the community and social development campaigns; planning legal framework and enforcement.